What drives capacity to innovate? Insights from women and men small-scale farmers in Africa, Asia and Latin America - Badstue, Lone B. (International Maize and Wheat Improvement Center, 2018)
Presented by Lone Badstue (CIMMYT), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.